Real-time active and reactive power regulation in power systems with tap-changing transformers and controllable loads - Zhang, X; Kang, R; McCulloch, M; Papachristodoulou, A (Elsevier, 2015)
Due to increasing uncertainties resulting from renewable energy penetration and variability in both supply and demand, the control and economic optimization for power networks will need to run on faster time-scales. Moreover, distributed and decentralized control architectures are necessary as power systems are distributed large-scale networks with a lot of complexity, which makes centralized control expensive, inefficient and hard to implement. In this paper, the problem of real-time active and reactive power regulation for power networks with controllable loads and tap-changing transformers is considered. First, the state-space model of a transmission level network under exogenous disturbances is obtained, which is decomposed into two subsystems, describing frequency and voltage dynamics respectively. For the subsystem describing frequency dynamics, an optimization problem relating to active power regulation is first formulated. A distributed controller is then proposed and its optimality, stability and delay robustness are studied. Also, nonlinear proportional actions for controllable loads are introduced to improve the performance of the subsystem. For the subsystem describing voltage dynamics, simple integral control is used for controllable loads and the asymptotic stability of the closed-loop subsystem is shown. To implement the reactive power regulation scheme, a method for local users to detect the tap position variation of the On-Load Tap Changer (OLTC) at the bus they are connected to is presented. Thus, the overall load control scheme is completely decentralized and can be applied easily. Numerical investigations illustrate the performance of the combined active and reactive power regulation scheme.